METODE OUTDOOR LEARNING TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPTIF - -, Surendi; Fitriyani, Kamila Cahya; Balqis, Putri (Kurikula : Jurnal Pendidikan, 2025)
This study aims to analyze the effect of the outdoor learning method on the descriptive writing skills of fifth-grade students at SDN Jasinga 06. This research employs a quantitative approach with a one-group pretest-posttest design, involving 16 students tested before and after the implementation of this method. Data were collected through descriptive writing tests and analyzed using descriptive statistical tests and t-tests with SPSS. The results indicate a significant increase in the average score from 45.625 in the pre-test to 75 in the post-test. The t-test confirms that this method has a significant impact on improving students' writing skills. Outdoor learning provides a direct learning experience by allowing students to observe, perceive, and describe objects more vividly, making their writing more detailed and structured. In addition to enhancing writing skills, this method helps students expand their vocabulary and gain a deeper understanding of descriptive concepts. Therefore, this method is recommended as an innovative approach in Indonesian language education at the elementary school level, particularly in improving descriptive writing skills.